Prevention is better than cure: Understanding metabolic syndrome (MetS) and the occupational risks for perioperative nurses - Turnbull, Daniel; Foran, Paula (Operating Room Nurses Association of Canada Journal, 2024)
Metabolic syndrome (MetS) is a condition with interconnected abnormalities of the metabolic system that has been labelled by the World Health Organization as a main cause of death worldwide. Risk factors for MetS include occupational stress, disturbances to circadian rhythms, sleep disorders and changed eating habits, which are all associated with shift work. As shift work and occupational stress are common in perioperative nursing, the risk of developing MetS is increased for perioperative nurses. This discussion paper aims to bring an awareness and understanding of MetS to perioperative nurses and identifies the occupational risks in the perioperative environment that may lead to its development. It also presents some possible strategies to mitigate the risk factors or prevent this condition for perioperative nurses in the future.